The transformation of historical research in the digital age - Milligan, Ian, 1983- (Cambridge University Press, 2022)
Historians make research queries on Google, ProQuest, and the HathiTrust. They garner information from keyword searches, carried out across millions of documents, their research shaped by algorithms they rarely understand. Historians often then visit archives in whirlwind trips marked by thousands of digital photographs, subsequently explored on computer monitors from the comfort of their offices. They may then take to social media or other digital platforms, their work shaped through these new forms of pre- and post-publication review. Almost all aspects of the historian's research workflow have been transformed by digital technology. In other words, all historians - not just Digital Historians - are implicated in this shift. The Transformation of Historical Research in the Digital Age equips historians to be self-conscious practitioners by making these shifts explicit and exploring their long-term impact. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 31 Aug 2022).
Keywords: History -- Methodology.; History -- Research -- Data processing.; Digital humanities.